Should it really be that hard to model the chirality induced spin selectivity effect? - Fransson, Jonas (APL Computational Physics, 2025)
The chirality induced spin selectivity effect remains a challenge to capture with theoretical modeling. While at least a decade was spent on independent electron models, which completely fail to reproduce the experimental results, the lesson to be drawn out of these efforts is that a correct modeling of the effect has to include interactions among the electrons. In the discussion of the phenomenon, one inevitably encounters the Onsager reciprocity and time-reversal symmetry and questions whether the observations violate these fundamental concepts or whether we have not been able to identify what it is that makes those concepts redundant in this context. The experimental fact is that electrons spin-polarize by one or another reason when traversing chiral molecules. The setups are simple enough to enable effective modeling; however, overcoming the grand failures of the theoretical efforts, thus far, and formulating a theory that is founded on microscopic modeling appears to be a challenge. A discussion of the importance of electron correlations is outlined, pointing to possible spontaneous breaking of time-reversal symmetry and Onsager reciprocity.